2022
DOI: 10.21203/rs.3.rs-2165323/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The OptiBreech Care Pathway: evaluating the feasibility and acceptability of team care for women seeking to plan a vaginal breech birth (OptiBreech 1) – a mixed methods implementation feasibility study

Abstract: Background OptiBreech Care is a care pathway for breech presentation at term, including where chosen, physiological breech birth attended by professionals with advanced training and/or proficiency. We aimed to assess the feasibility of implementing OptiBreech team care to test it in trial-within-a-cohort study. Methods Our design was a mixed methods trial feasibility assessment across England and Wales, January 2021 – June 2022. Our objectives were to determine whether Trusts could provide attendants with a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Across three studies, one serious adverse neonatal outcome has been reported (0.5%). [3][4][5] This is very near to the rate of adverse outcomes observed among low-risk women planning cephalic (head-first) births in the UK. Neonatal admission rates have been below 5%, similar to rates for all term births in the UK.…”
Section: Dear Editormentioning
confidence: 85%
See 2 more Smart Citations
“…Across three studies, one serious adverse neonatal outcome has been reported (0.5%). [3][4][5] This is very near to the rate of adverse outcomes observed among low-risk women planning cephalic (head-first) births in the UK. Neonatal admission rates have been below 5%, similar to rates for all term births in the UK.…”
Section: Dear Editormentioning
confidence: 85%
“…The complex intervention being tested, OptiBreech collaborative care, has been built up from over a decade's worth of research into howin the current conditions you describepractitioners acquire VBB skill and experience. [3][4][5] As you say, the conditions that (arguably) enabled this in the past are now non-existent. Different times call for different thinking and different strategies.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation